MODIFICATION OF JURGEN HABERMAS THOUGHT IN BUSINESS MANAGEMENT PRACTICES: AN EMPIRICAL STUDY AT MONDRAGON CORP - Saputra, Andhika Rahmat; Robbie, R Iqbal; Bangun, M. Fitrah Ashary (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
This study aims to briefly review the thoughts of Jurgen Habermas, the German philosopher at the Frankfurt School of Religion with his critical philosophy, especially those concerning social thoughts by comparing them to management science so that management science in theory and practice can be critical. Data processing uses descriptive analysis with a deconstruction paradigm, looking more sharply to give new and critical meanings to the interpretation of Habermas' thought. The text is understood and rearranged from a different perspective of thought, after discovering the foundation and philosophical structure of Habermas' thought, the researcher contributes thoughts in management science so that he can include it in the implementation of the Mondragon company. The results of this study prove that the idea of critical management science supports people's views regarding profitability and the strategy of the Mondragon company in a brief conceptualization reflecting the vision, mission, and values that adhere to humanity, equality of emancipatory values , and solidarity. The managerial implications are addressed by methods that are democratic and prioritize the social side to increase profitabilityKeywords: habermas, strategic management, democratic, mondragon